A rechargeable high-temperature molten salt iron-oxygen battery - Peng, Cheng; Guan, Chengzhi; Lin, Jun; Zhang, Shiyu; Bao, Hongliang; Wang, Yu; Xiao, Guoping; Chen, George Zheng; Wang, Jianqiang (Wiley-VCH Verlag, 2018)
The energy and power density of conventional batteries are far lower than their theoretical expectations, primarily because of the slow reaction kinetics in the battery that is often working under ambient conditions. Here we describe a low-cost and high-temperature rechargeable iron-oxygen battery containing a bi-phase electrolyte of molten carbonate and solid oxide. This new design merges the merits of solid oxide fuel cell and molten metal-air battery, offering significantly improved battery reaction kinetics and hence the power capability without compromising the energy capacity. The as-fabricated battery prototype can be charged at high current density, and exhibit excellent stability and security in highly charged state without self-discharge. It typically exhibits 129.1 Wh kg-1 in specific energy and 2.8 kW kg-1 in specific power, and 388.1 Wh L-1 in energy density and 21.0 kW L -1 in power density based on the mass and volume of the molten salt, respectively.